PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUGMENTED REALITY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS IPA SISWA SD - Oktafrina, Andhini; Suwangsih, Erna; Permas Hikmatunnisa, Nenden (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted with the aim of examining the effect and improvement of using the Discovery Learning model supported by Augmented Reality media to enhance critical thinking skills in elementary school students.In 21st-century learning, both teachers and students face the challenges of globalization. Students tend to focus more on memorizing material and formulas rather than understanding the essence of the learning process.In addition the lack of variation in learning models, methods, and media also negatively affects students’ thinking abilities..The research method used was a quasi-experimental design. The subjects involved two groups: an experimental group that received Discovery Learning supported by Augmented Reality media, and a control group that received conventional instruction. Based on data analysis, a significant difference was found in the improvement and effect on critical thinking skills between the two groups. These findings indicate that the Discovery Learning strategy integrated with Augmented Reality media is effective in helping students think critically. The Discovery Learning model showed an effect and improvement of 21% in enhancing students’ critical thinking skills.